Author Correction: Traps and transport resistance are the next frontiers for stable non-fullerene acceptor solar cells (Nature Communications, (2022), 13, 1, (3786), 10.1038/s41467-022-31326-z) - Wöpke, Christopher; Göhler, Clemens; Saladina, Maria; Du, Xiaoyan; Nian, Li; Greve, Christopher; Zhu, Chenhui; Yallum, Kaila M.; Hofstetter, Yvonne J.; Becker-Koch, David; Li, Ning; Heumüller, Thomas; et al. (Nature Communications, 2022)
The original version of this Article contained an error in Fig. 2, in which three data sets (represented by circles, squares and triangles, respectively)were shifted along the x-axis by one data point, leadin g to an incorrect representation of the “Exp. suns-Voc” data (the symbols) in Fig. 2a and 2b. The correct version of Fig. 2 is:(Figure Presented.).This has been corrected in both the PDF andHTMLversions of the Article.
CRIS-Team Scopus Importer:2022-08-12